Analisis Kesulitan Belajar Matematika dalam Menyelesaikan Soal Cerita di Kelas IV Sekolah Dasar Negeri Pakujaya 02 - Amaliyah, Aam; Maulida, Luthfia Nur; Safitri, Nabilah Dwi; Dewi, Ratri Hersita; Septiara, Sabgi Wulan (Lembaga Yasin AlSys, 2022)
Students with learning difficulties in mathematics often make mistakes in solving story problems on fractional material. This research uses descriptive qualitative. The purpose of this study was to determine the types of learning difficulties in mathematics experienced by students, the factors that influence learning difficulties, and to reveal the efforts that can be made to overcome the difficulties in learning mathematics in grade IV Pakujaya 02 State Elementary School. Data collection techniques were observation and interviews. . Based on data analysis and discussion, students experienced errors, namely: 1. Understanding the problem, namely errors in interpreting language and making mathematical models. The reason is incomplete/wrong reasoning and low student ability. 2. Planning for problem solving is an error in connecting one concept with another concept. The cause of this error is the humanistic thinking of students. 3. Implement problem solving planning, namely errors in implementing incorrect formulas. Errors in this aspect are caused by incomplete or incorrect reasoning and students' humanistic thinking.